Tsetse fly inspired steerable bone drill—a proof of concept - de Kater, Esther P.; Müller, Rob; Sakes, Aimée; Breedveld, Paul (Frontiers in Bioengineering and Biotechnology, 2023)
The fixation strength of pedicle screws could be increased by fixating along the much stronger cortical bone layer, which is not possible with the current rigid and straight bone drills. Inspired by the tsetse fly, a single-plane steerable bone drill was developed. The drill has a flexible transmission using two stacked leaf springs such that the drill is flexible in one plane and can drill along the cortical bone layer utilizing wall guidance. A proof-of-principle experiment was performed which showed that the Tsetse Drill was able to successfully drill through 5, 10 and 15 PCF cancellous bone phantom which has similar mechanical properties to severe osteoporotic, osteoporotic and healthy cancellous bone. Furthermore, the Tsetse Drill was able to successfully steer and drill along the cortical wall utilizing wall guidance for an insertion angle of 5o, 10o and 15o. The experiments conclude that the tsetse fly-inspired drilling method is successful and even allows the drilling along the cortical bone layer. The Tsetse Drill can create curved tunnels utilizing wall guidance which could increase the fixation strength of bone anchors and limit the risk of cortical breach and damage to surrounding anatomy.